ANALYSIS OF DATA ROUTING STRATEGIES FOR WIRELESS SENSOR NETWORKS - PYRIH, YAROSLAV; PYRIH, YULIIA (Herald of Khmelnytskyi National University. Technical sciences, 2025)
Amid the rapid development of information and communication technologies, there is an increasing demand for efficient and reliable data routing in next-generation computer and telecommunication systems. Wireless Sensor Networks (WSNs), which are widely applied across various domains – from environmental monitoring to healthcare and industrial automation – require a customized approach to routing strategy selection due to their constrained energy resources, dynamic topologies, and high node densities. Given the growing diversity of network architectures and the rising performance requirements, it becomes essential to identify optimal routing mechanisms capable of balancing delivery latency, throughput, energy consumption, and fault tolerance. This paper presents a structured review and analysis of recent studies dedicated to data transmission characteristics in WSNs. Particular attention is given to the importance of routing strategy classification in the context of designing an efficient WSN architecture, as it enables not only the systematization of existing solutions but also the justification of the most appropriate approach based on the network parameters. A comprehensive classification of routing strategies is shown, including: by route discovery method (proactive, reactive, hybrid), by network architecture (flat, hierarchical, location-based); by operational model (multipath, query-based, negotiation-based, QoS-based, and data-centric (further categorized into coherent and non-coherent approaches); by communication initiator (source-based and destination-based). The study explores the implementation specifics of each strategy, highlighting their advantages and potential limitations in the context of WSNs operating under energy and computational constraints. It has been found that the choice of an appropriate routing strategy significantly affects data transmission efficiency, network stability, delivery delays, and energy expenditure – key parameters for the practical deployment of WSNs across application areas ranging from environmental monitoring to industrial systems. The results obtained in this review may be used to improve routing algorithms and adapt them to specific operational conditions of sensor networks.
Keywords: routing; wireless sensor network; classification; sensor node